THE RELATIONSHIP BETWEEN STOCK RETURN AND INFLATION IN NIGERIA - Ibrahim, Taofik Mohammed; Agbaje, Omosola M. (European Scientific Journal, ESJ, 2013)
﻿This study examines the long-run relationships and dynamic interactions between stock returns and inflation in Nigeria using monthly data of the All Share Price Index from the Nigerian Stock Exchange and Nigerian Consumers Price Index from January 1997 to 2010. The analytical technique of Autoregressive Distributed Lag (ARDL) bound test as proposed by Pesaran and Pesaran (1997); and Pesaran et. al. (2001) was exploited. From the results, it is evident that there is the existence of a long run relationship between stock returns and inflation. The short run dynamic model also reveals that the speed of convergence to equilibrium is moderate implying that there is a short run relationship between stock returns and inflation. This is attributable perhaps to the instability of prices of stocks noticed over time.